Expression of National Thought in the Story - Gairat Murodov; Zarina Jalilova (Researchparks Publishing, 2022)
In the prose`s artistic development of modern Uzbek literature, especially prose, the well-known writer, poet, dramatist, artist of the Republic of Uzbekistan, winner of the State Prize Amon Mukhtar has a unique place and special services. The author has been engaged in literary activity for more than fifty years. During this time, he wrote hundreds of poems, poems, stories, several dramas, short stories, and about twenty novels. Most of his novels were created during the years of national independence.